(3TQM GdJdhjMGJ ddSgQhOis - (3SYO Hf efUhQ Hf SYO Hf GdMSf Hf gHI Gddg Hf cehfI GdGSQGFjdj, YR GdOhdI,J (B676 (3g` s; (3GdTgGH GdSgQhQOj , TgGH GdOjf CHh GdaJhM,J (B587 (3g` s ((3ESeGYjd Hf EHQGgje Hf GdRGgO s)
(3BNQgG (B:s
(3jfJgi (B" (3HBNQ TQM GdYde GdWHjYi (B" s
(3GdfSNI HgG MhGTs
(3fSNI QGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdadSaI hGdefWbs